PENINGKATAN KEMAMPUAN BERHITUNG ANAK MELALUI PERMAINAN MAZE ANGKA PADA KELOMPOK A DI RA AL QUR’AN EL AZZAM PARIT MALINTANG KABUPATEN PADANG PARIAMAN - Rosita Ariani; Juliwis Kardi; Mega Cahya Dwi Lestari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The counting skills of children at RA Al Qur'an El Azzam Parit Malintang, not yet optimum. One of them is a learning medium that is less intersting. The media used are number posters, writing on the blackboard, and there are children who are not yet able to differentiate number symbols, counting numbers in sequence, connecting the amount of objects with number symbols, still reversed in writing. This study aims to determine the process of children's activities through number maze games and to determine the extent to which children's counting abilities improve through number maze games.The method used the research is Classroom Action Research (CAR) which utilised two cycles in implementing the number maze game. This research was carried out in the first semester of the 2025/2026 academic year with amount 13 children consisting of 6 girls and 7 boys. The data accumulation techniques in this research are observation, interviews, and documentation. The results this study conclude that number maze activity can improve children's counting skills. The first Cycle I was conduct 3 time meetings, for the first meeting 38%, second meeting 50% and third meeting 59%. In second cycle, the first meeting was 63%, second meeting 71%, and the third meeting 81%. In conclusion this research successfull to improve childrens counting skills through number maze games.